A new intelligent power quality disturbance classification in renewable and decentralized hydrogen-based energy systems using SwResNET hybrid model - Kucuker, Ahmet; Barakli, Burhan; Bayrak, Gokay; Basaran, Kivanc; Balaban, Georgiana (Pergamon-Elsevier Science Ltd, 2025)
In this study, a scalogram image-based Swin-Residual Network (SwResNET) hybrid method is proposed for the identification of power quality disturbances (PQDs) in a hydrogen energy-based distributed generator (HEBDGs). The proposed approach involves the creation of PQD scalogram images by applying spectrogram analysis to power signal data. This process generates a two-dimensional image that represents the frequency and time characteristics of the signal. These spectrogram images are then input into a SwResNET hybrid model for learning. The SwResNET hybrid model extracts features from the scalogram images and classifies the input signal based on the presence or absence of power quality disturbances. This paper used 21 different PQD events in HEBDGs for classification purposes. Furthermore, the proposed method was tested under noisy conditions. The data achieved from simulated results of the HEBDG system in Matlab/Simulink and empirical data collected in the laboratory collectively demonstrate that the proposed methodology exhibits exceptional performance in terms of 98.22 % accuracy and resistance to noise, surpassing existing state-of-the-art approaches.
Keywords: Hydrogen energy-based distributed generation; Power quality disturbances; Swin transformer learning; Residual networks; Vision transformers